Differences in the interest rates of microfinance institutions in some markets economies: An HLM approach - Ramírez Rocha, Adriana; Bernal Ponce, L. Arturo; Cervantes Zepeda, Mauricio (Estudios Económicos de El Colegio de México, 2019)
In this study, we analyzed the differences in the interest rates of microfinance institutions (MFIs) of some countries in Latin America, Africa, Eastern Europe and Asia. We found that the operating expenses are essential drivers of these interest rates. We also found that operating expenses, average loan per borrower, real growth GDP, and government effectiveness, are key factors that explain differences in interest rates. We use apply Hierarchical Linear Modeling (HLM) to analyze these differences.